The impact of climate engagement: A field experiment - Florian Heeb; Julian Kölbel (Leibniz Institute for Financial Research SAFE, 2024)
We report results from a pre-registered field experiment about the impact of index provider engagement on corporate climate policy. A randomly chosen group of 300 out of 1227 international companies received a letter from an index provider, encouraging the company to commit to setting a science-based climate target to remain included in its climate transition benchmark indices. After one year, we observed a significant effect: 21.0% of treated companies have committed, vs. 15.7% in the control group. This suggests that engagement by financial institutions can affect corporate policies when a feasible request is combined with a credible threat of exit.
Keywords: D22; D62; G23; G34; M14; 330; Shareholder Engagement; Field Experiment; Climate; ESG; Activism